Corporate Social Responsibility Reporting and Financial Performance - Chikobvu, Irene (Graduate School of Business (GSB), 2024)
This study aims to investigate the relationship between corporate social responsibility (CSR) reporting and the financial performance of JSE-listed companies in South Africa. The study used annual cross-sectional data of 76 JSE-listed companies for the period 2012 to 2019, extracted from the Integrated Real-time Equity System (IRESS). CSR reporting data was obtained from companies' annual reports. The panel data model was estimated using the twostage least squares instrumental variable technique to account for endogeneity. From the analysis, approximately 80.3% of companies included in the study reported on CSR, with the majority (46.7%) of these companies are from the industrials sector. After controlling for endogeneity using random effects models, the relationship between CSR reporting and ROA and PM was statistically significant at p=0.056 and p=0.109 for ROA and PM respectively, suggesting CSR reporting firms are associated with improved financial performance. Stakeholder and legitimacy theories are supported by these findings. Therefore, a company must consider the interests of all its stakeholders - direct or indirect - given that a company's survival depends on the extent to which it operates within the boundaries and norms of society. The researcher recommended that JSE-listed companies consider reporting on CSR as an enabler for a firm's financial performance